Phospholipase D6 activates Wnt/β-catenin signaling through mitochondrial metabolic reprogramming to promote tumorigenesis in colorectal cancer - Hyun Ji Lee; Seong Hun Lim; Hyesung Lee; Jung Min Han; Do Sik Min (Experimental and Molecular Medicine)
Abstract Phospholipase D6 (PLD6) is a critical enzyme involved in mitochondrial fusion with a key role in spermatogenesis. However, the role of PLD6 in cancer remains unknown. Notably, Wnt signaling, energy metabolism and mitochondrial function show complex interactions in colorectal cancer (CRC) progression. Here we found that PLD6 is highly expressed in CRC and positively correlated with poor prognosis. We present a novel function of PLD6 in activating Wnt/β-catenin signaling by enhancing mitochondrial metabolism. PLD6 depletion suppresses the oncogenic properties of CRC cells and impairs mitochondrial respiration, leading to reduced mitochondrial length, membrane potential, calcium levels and reactive oxygen species. PLD6 depletion also disrupts mitochondrial metabolic reprogramming by inhibiting the tricarboxylic acid cycle and mitochondrial oxidative phosphorylation, resulting in altered intracellular levels of citrate and acetyl-CoA—both key modulators of Wnt/β-catenin activation. PLD6-mediated acetyl-CoA production enhances β-catenin stability by promoting its acetylation via the acetyltransferases CREB-binding protein and P300/CREB-binding-protein-associated factor. Consequently, PLD6 ablation reduces cancer stem cell-associated gene expression downstream of Wnt/β-catenin signaling, suppressing stem-like traits and chemoresistance to 5-fluorouracil. Furthermore, PLD6 depletion attenuates CRC tumorigenesis in both subcutaneous and orthotopic tumor models. Overall, PLD6 acts as an oncogenic switch by promoting mitochondria-mediated retrograde signaling, thereby regulating Wnt signaling in CRC.